Experimental study on the effect of prefabricated fissures on the creep mechanical properties and acoustic emission characteristics of sandstone under uniaxial compression - Yu, Huaichang; Wang, Guanqiang; Zhang, Zhongyu; Niu, Rui; Cheng, Guangli (Frontiers in Earth Science, 2022)
This study investigates the effect of prefabricated fissures on the creep mechanical strength and acoustic emission (AE) characteristics of sandstone. Under the same test conditions, indoor uniaxial compression creep AE tests were performed on intact and artificially fissured sandstone specimens using a rock rheometer and a PCI-Ⅱ AE tester controlled with an RLJW-2000 microcomputer. The variation characteristics of strain, long-term strength, number of AE events, AE ringing count, AE energy, and RA value of the two specimens were then analyzed to determine the effect of prefabricated fissures on the creep mechanical properties and AE characteristics of sandstone. The results show that under the same stress level, the instantaneous strain, creep strain, and total strain of the prefabricated fissures specimen was larger than the corresponding values of the intact specimen. The prefabricated fissures exhibited the most significant influence on the creep strain of the specimen, followed by the total strain. The fissures showed the least influence on the instantaneous strain of the specimen. Furthermore, the long-term strength of the prefabricated fissures specimen was only 37.5% of that of the intact specimen. Owing to the influence of the prefabricated fissures, the long-term strength of the sandstone was significantly reduced. In engineering practice, fissures should be noted and analyzed for the potential failure of a formation. Moreover, as the stress level increases, the number of AE events of the specimen also increases. The number of AE events and cumulative AE events generated by the prefabricated fissures specimen at various stress levels is significantly higher than the corresponding values of the intact specimen. The maximum ringing count of the prefabricated fissures specimen was 7.3 times that of the intact specimen, and the maximum AE energy was 3.8 times that of the intact specimen. The cumulative AE ringing count was 1.5 times that of the intact specimen, and the cumulative energy was 4.5 times that of the intact specimen. The prefabricated fissures significantly affect the maximum AE ringing count, maximum AE energy, cumulative AE ringing count, and cumulative AE energy of the specimen. Finally, tensile fissures were the main microcracks generated inside the intact specimen during creep, and shear cracks were secondary. The microcracks generated inside the prefabricated fissures specimen consisted of mixed tension-shear cracks, but mainly consisted of shear cracks with fewer tension cracks. The RA value correlates well with the observed internal microcracks, indicating that the RA value can be used to characterize fractures in sandstone specimens. The RA value has a guiding significance for characterizing the type of internal microcracks in the process of rock creep.